Innovations in Agricultural Biotechnology for Sustainable Crop Production - Almira Ulimaz; Jesi Yardani; Dewi Amelia Widiyastuti (Research of Scientia Naturalis, 2024)
Global agriculture faces challenges such as climate change, soil degradation, and increasing food demand, necessitating innovative solutions for sustainable crop production. Agricultural biotechnology offers advanced tools to enhance crop resilience, improve yield, and reduce environmental impacts. This study aims to explore recent innovations in agricultural biotechnology, focusing on their potential to support sustainable crop production under diverse environmental conditions. The research employs a systematic literature review method, analyzing recent studies on genetic engineering, genome editing (CRISPR-Cas9), biofortification, and biopesticides. The review covers both laboratory and field trials to evaluate the effectiveness of these biotechnologies in improving crop traits such as drought tolerance, pest resistance, and nutritional quality. Key aspects considered include technological efficiency, scalability, and ecological impacts. Results indicate that innovations like CRISPR-Cas9 have significantly enhanced crop resilience, with increased drought tolerance and pest resistance observed in crops like maize, wheat, and rice. Biofortification has improved the nutritional quality of staple crops, addressing micronutrient deficiencies. The integration of biopesticides has reduced the reliance on chemical pesticides, contributing to more sustainable farming practices. The study concludes that agricultural biotechnology innovations hold significant promise for achieving sustainable crop production. However, their successful implementation requires supportive policies, farmer education, and ongoing research to ensure safety, scalability, and environmental compatibility. The findings highlight the need for a holistic approach to integrate biotechnological advancements into mainstream agriculture for long-term sustainability.